Evaluation of the Suitability of Middle Miocene Aquifer Water for Agriculture in the Western Coastal Region of Libya - د . عبد السلام محمد الراجحي (African Journal of Advanced Pure and Applied Sciences, 2025)
This study aims to evaluate the water potential of the Middle Miocene aquifer in the western coastal region by analyzing its geological, hydrogeological, and chemical characteristics, and by comparing its water quality with that of the highly saline Quaternary aquifer. The study relied on field and laboratory data collected from exploited wells and analyzed using scientific indicators such as Sodium Percentage (Na%), Sodium Adsorption Ratio (SAR), and Electrical Conductivity (EC), in addition to international classifications (Wilcox, Richards, FAO) to assess water suitability for agricultural purposes. The results revealed that the Middle Miocene aquifer water is characterized by lower salinity and higher productivity compared to the Quaternary aquifer, with TDS values ranging between 3,500–5,000 mg/L. Na% and SAR values fell within acceptable limits, reflecting its potential use in agriculture, particularly in soils with good permeability. Practical experiments in the Al-‘Assa agricultural project and center-pivot irrigation demonstrated successful cultivation of olive, date palm, and pomegranate using this water, while salt-sensitive crops showed weak performance. Accordingly, the study confirms that the Middle Miocene aquifer represents a practical and sustainable alternative to the Quaternary aquifer and constitutes a promising source for agricultural and economic development in the region, provided that appropriate salinity management practices are applied to ensure the sustainability of this water resource.